2022
DOI: 10.1016/j.euros.2021.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Renal Morbidity Following Radical Cystectomy in Patients with Bladder Cancer

Abstract: Take Home Message Increasing age, pre- and postoperative hydronephrosis, impaired baseline kidney function, and adjuvant chemotherapy contribute to significant kidney function decline following radical cystectomy. Nearly one-third of patients develop advanced chronic kidney disease within a year of radical cystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…15 Eisenberg et al reported the first study evaluating renal function with long-term follow up in a large cohort following RC and urinary diversion. 16 They reported that the renal function decline approximately 49% and 72% at 5 and 10 years respectively. In present study also there was decline of renal function in range of 10-1 ml/h eGFR in 61.3% of the patients whereas decline of renal function >10 ml/h eGFR in 3.9% of the patients over 62 months of median follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…15 Eisenberg et al reported the first study evaluating renal function with long-term follow up in a large cohort following RC and urinary diversion. 16 They reported that the renal function decline approximately 49% and 72% at 5 and 10 years respectively. In present study also there was decline of renal function in range of 10-1 ml/h eGFR in 61.3% of the patients whereas decline of renal function >10 ml/h eGFR in 3.9% of the patients over 62 months of median follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…While few studies stratified their analysis of eGFR change by chemotherapy administration, the use of perioperative chemotherapy was frequently examined in multivariable analyses. These revealed an inconsistent relationship with decline in eGFR, [20][21][22][23][24][25][26][27] with the majority not finding a significant relationship (Table 4). This is perhaps unsurprising given the difficulty of adjusting for the multitude of interconnected confounding factors that may affect renal function in patients undergoing RC.…”
Section: Discussionmentioning
confidence: 99%
“…Across several studies, the mean eGFR decline one year post-RC ranged from 2-10 mL/min/1.73 m 2 , with perioperative chemotherapy usage rates varying from 11-41%. [20][21][22][23][24][25][26][27] In a study of 1631 patients where only 12% received perioperative chemotherapy, the mean eGFR decline at one year was 5 mL/min/1.73 m 2 . 22 In a separate study by Chandrasekar et al, 24 the mean eGFR decline of 175 patients who underwent RC without NAC was 1.6 mL/min/1.73 m 2 one year after surgery, whereas it was 19.1 mL/min/1.73 m 2 in the 66 who received cisplatin NAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation